Improved vaccine efficacy of tumor exosome compared to tumor lysate loaded dendritic cells in mice - Gu, Xiaoyu; Erb, Ulrike; Büchler, Markus W.; Zöller, Margot (International journal of cancer, 2015)
Leukemia immunotherapy frequently does not meet expectation, one of the handicaps being tumor exosome (TEX)-promoted immunosuppression. We here asked, using the mouse myeloid leukemia WEHI3B and the renal cell carcinoma line RENCA, whether dendritic cell (DC) vaccination suffices to counterregulate TEX-induced immunosuppression and whether TEX could serve as tumor antigen for DC-loading. DC-vaccination significantly prolonged the survival time of WEHI3B-bearing mice, TEX-loaded DC (DC-TEX) being superior to lysate-loaded DC (DC-lys), even an excess of TEX not interfering with immune response induction. The superior response to DC-TEX was accompanied by an increase in WEHI3B-specific CD4+ T cells, evaluated by trogocytosis and proliferation. Similar findings accounted for DC loaded with RENCA TEX. TEX was efficiently taken-up by DC and TEX uptake supported CD11c, MHCII and IL12 upregulation in DC. Importantly, TEX was partly recruited into the MHCII-loading compartment such that “TEX” presentation time and recovery in T cells significantly exceeded that of tumor-lysate. Thus, TEX did not drive DC into a suppressive phenotype and were a superior antigen due to higher efficacy of TEX-presentation that is supported by prolonged persistence, preferential processing in the MHCII-loading compartment and pronounced trogocytosis by T helper cells. TEX is present in tumor patients' sera. TEX, recovered and enriched from patients' sera, might well provide an optimized, individual-specific antigen source for DC-loading and vaccination.